2011
DOI: 10.1111/j.1432-2277.2011.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic bladder substitute in renal transplant recipients: experience with Studer technique and literature review

Abstract: Summary Renal transplant recipients with high‐risk bladder cancer following cystectomy need a urinary diversion preserving the renal function and possibly maintaining body image, while still offering the best oncological outcome. The aim of this report is to describe our experience of radical cystectomy and orthotopic ileal neobladder with Studer technique in this population, and to review the literature. We performed radical cystectomy and Studer ileal neobladder in four male patients (median age 67 years) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Similarly to reports by many other authors, we prefer reconstructive surgeries before RTx to avoid the possible adverse effects of immunosuppression, such as delayed wound healing and severe infection, in addition to the prevention of any harmful effect of LUTD on the graft [16,19]. It may not always be necessary to intervene in patients with borderline bladder compliance, however, as a small non-compliant bladder may improve after transplantation in some cases after restoration of urinary flow, sparing the patients a reconstructive surgery [10,21,22]. This requires close follow-up after transplantation to continuously assess the bladder and decide early on augmentation if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to reports by many other authors, we prefer reconstructive surgeries before RTx to avoid the possible adverse effects of immunosuppression, such as delayed wound healing and severe infection, in addition to the prevention of any harmful effect of LUTD on the graft [16,19]. It may not always be necessary to intervene in patients with borderline bladder compliance, however, as a small non-compliant bladder may improve after transplantation in some cases after restoration of urinary flow, sparing the patients a reconstructive surgery [10,21,22]. This requires close follow-up after transplantation to continuously assess the bladder and decide early on augmentation if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Manassero et al identified four patients who had Studer neobladder formation after RC for bladder cancer. 13 Two patients died of disease at 14 and 20 months, while the remaining two patients are alive without disease at 36 and 56 months followup. They reported satisfactory day and nighttime continence in all patients.…”
Section: Discussionmentioning
confidence: 95%
“…12,13,15 Kamal et al reported 5 patients who underwent either urethral hemi-Kock pouch formation or Hautmann-type neobladder diversion with serous lined extramural tunnels. 12 Two patients with pT3 disease died of metastasis at 3 and 14 months, one died of cerebrovascular accident at 14 months, and the remaining two were alive without disease at 28 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ileal conduit formation, and continent cutaneous diversion) and orthotopic substitution for these patients. In several recent reports, continent cutaneous diversion and orthotopic substitution showed good functional and safe outcomes [13,14,15]. However these surgeons mainly chose staged operations.…”
Section: Discussionmentioning
confidence: 99%